Four Years of Trump The US and the World - Mario Del Pero (ISPI Publications, 2020)
Unprecedented and unpredictable: this is how US President Donald Trump's administration has repeatedly been labelled during its first term. Beyond the frequent tweets and bombastic rhetoric, however, lie a more conventional four years, as the United States navigated an ever-evolving international reality, compounded by a global pandemic and one of the deepest economic recessions in over a century. This Report analyses the continuity and changes that occurred during Trump's first term. Domestically, it investigates the growing political polarization, the country's pre-pandemic economic performance, Trump's approach towards regular and irregular migration, and the US' response to a healthcare emergency. At the international level, this volume looks at how the US stance has changed vis-à-vis China, the Middle East, and Europe. Which long-term trends has President Trump had to ride through? What was his trademark, and what might be his lasting legacy?